Measuring quality for destination marketing: local public stakeholders’ perceptions in Portugal - Andreia Filipa Antunes Moura; Lisete Santos Mendes Mónico; Maria do Rosário Campos Mira (Tourism & Management Studies)
Based on academic research and international recommendations on tourism quality, this study sought to develop a wide-ranging tourism quality scale adapted for Portuguese contexts. The research included creating and validating a marketing subscale to measure local public stakeholders’ perceptions of marketing strategies focused on improving tourism destinations’ quality. A self-administered survey was conducted with a sample of Portuguese municipalities including, more specifically, 134 local public stakeholders commonly considered local destination marketing organisations, as well as public policy- and decision-makers. Exploratory and confirmatory factor analyses were performed to measure destination marketing quality, resulting in the identification of two factors: (1) image and promotion and (2) product differentiation. The proposed instrument was shown to have validity and reliability and to be a useful measurement tool. The findings highlight local public stakeholders’ responsibility to ensure the quality and competitiveness of tourism destinations’ marketing and provide multiple useful practical and theoretical implications and insights to guide future research.